2019
DOI: 10.1088/2399-6528/ab496f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing temperature on structural morphological and optical properties of spray pyrolized Al-doped ZnO thin films

Abstract: Aluminium doped zinc oxide (AZO) thin films were prepared on glass substrate by spray pyrolysis technique and subsequently their structural, morphological and optical properties were investigated and analyzed as a function of annealing temperature. The films were deposited at 350°C and were annealed at temperature 350, 400, 450 and 500°C. X-ray diffraction (XRD) analysis confirms that both deposited and annealed films are polycrystalline in nature and have hexagonal wurtzite structure. The crystalline size as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 25 publications
3
12
0
Order By: Relevance
“…The shape of the annealed sample particles in Figure 3 (b-d) is almost not uniform as evidenced by the presence of flower-like particles. These results are similar to the research conducted by Kabir et al [12]. The size of the ZnO particle diameter is presented in Table 2.…”
Section: Surface Morphologysupporting
confidence: 91%
“…The shape of the annealed sample particles in Figure 3 (b-d) is almost not uniform as evidenced by the presence of flower-like particles. These results are similar to the research conducted by Kabir et al [12]. The size of the ZnO particle diameter is presented in Table 2.…”
Section: Surface Morphologysupporting
confidence: 91%
“…The effect of annealing temperature on the structural, morphological, and optical properties of spray-pyrolized Al-doped ZnO thin films was systematically investigated by Kabir et al [48]. It was shown that the annealing temperature affects the optical transmittance of the Al-doped ZnO thin films with the average transmittance value within the visible region found to be 70.3% for the as-deposited film [48]. indium tin oxide (ITO) substrate in the visible region was reported by Chen et al [47].…”
Section: Crystals 2019 9 X For Peer Review 6 Of 11mentioning
confidence: 99%
“…Solid substrates include conducting and non-conducting substrates (Hasani et al 2019). Conducting substrates include transparent conducting oxide (TCO) substrates such as indium tin oxides (ITO), fluorine-doped tin oxide (FTO) and zinc oxide (ZnO) and metal substrates such as Ag, Au and Si (Kabir et al 2019). Non-conducting substrates include amorphous substrate (glass), crystalline substrate (quartz) and flexible substrate (mica).…”
Section: Introductionmentioning
confidence: 99%
“…Non-conducting substrates include amorphous substrate (glass), crystalline substrate (quartz) and flexible substrate (mica). Substrate can be used as a thin-film supporter or as a current collector in different energy applications (Ngamsinlapasathian et al 2006;Hasani et al 2019;Kabir et al 2019).…”
Section: Introductionmentioning
confidence: 99%